Needle stick and sharp injuries (NSSIs) among housekeepers in a Saudi hospital: An intervention study - Kandeel, Amina Yousef; El-Gilany, Abdel-Hady (International Journal of Infection Control, 2017)
Needle stick and sharp injuries (NSSIs) are a risk factor for blood-borne infections in healthcare facilities, yet they are preventable occupational hazards for health care workers. We estimated the frequency of NSIs among housekeeping workers compared with other healthcare workers and evaluated the effect of preventive measures to reduce these injuries in housekeeping workers. The study was conducted in one Saudi Arabian hospital in 2011. NSSIs were analyzed retrospectively and an intervention for housekeepers that included 43 sessions of education and increased resources and supervision was implemented in 2012. Evaluation measures included monitoring sharp disposal compliance, reports of improperly disposed sharps, use of heavy duty gloves, Hepatitis B vaccination, and the frequency of NSSIs during 2012 and 2013. Chi square and Fisher's exact tests were used for comparison between groups and pre-post intervention. In 2011 NSSIs rates were 17.8% for housekeeping staff, 3.7% for nurses and 1.3% for doctors, although injury frequency varied by department. Also, 15% of housekeepers were immune to HBV and 21% used heavy duty gloves during waste management. During 2012and 2013 NSSIs rate dropped significantly to 9.6% and 2.7% and HBV immunization increased to 78.1% and 100%; respectively. Heavy duty gloves usage improved to 100%. Improper sharp disposal reports decreased from 15.1% in 2012 to 5.5% in 2013. Sharp disposal compliance improved from 35.6% to 78.1% in 2012 and 2013; respectively. Continuous training of housekeepers about proper sharps disposal is the responsibility of infection control team. However, continuous monitoring along with continuous training programs and resources adequacy is needed to maintain this improvement.